BS EN 62841-3-14 AMDAB. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 3-14. Particular requirements for transportable drain cleaners (4th March 2022) - British Standards Institution,
No abstract available